1H chemical shift anisotropy: a high sensitivity solid-state NMR dynamics probe for surface studies?. Issue 7 (18th November 2022) - Southern, Scott A.; Liu, Da-Jiang; Chatterjee, Puranjan; Li, Yuting; Perras, Frédéric A.
Abstract : Solid-state NMR probes of dynamics often require the use of isotopic enrichment, which limits their scope. Proton chemical shift anisotropy can provide a sensitive alternative in certain cases. Abstract : Dynamics play significant roles in chemistry and biochemistry—molecular motions impact both large- and small-scale chemical reactions in addition to biochemical processes. In many systems, including heterogeneous catalysts, the characterization of dynamics remains a challenge. The most common approaches involve the solid-state NMR measurement of anisotropic interactions, in particular 2 H quadrupolar coupling and 1 H–X dipolar coupling, which generally require isotope enrichment. Due to the high sensitivity of 1 H NMR, 1 H chemical shift anisotropy (CSA) is a particularly enticing, and underexplored, dynamics probe. We carried out 1 H CSA and 1 H– 13 C dipolar coupling measurements in a series of model supported complexes to understand how 1 H CSA can be leveraged to gain dynamic information for heterogeneous catalysts. Mathematical descriptions are given for the dynamic averaging of the CSA tensor, and its dependence on orientation and asymmetry. The variability of the orientation of the tensor in the molecular frame, in addition to its magnitude and asymmetry, negatively impacts attempts to extract quantitative dynamic information. Nevertheless, 1 H CSA measurements can reveal useful qualitative insights into the motions of a particularly dilute site, such as from a surface species.